Analisis Keproaktifan Unit Manufaktur sebagai Pembeda Kinerja Perusahaan - Siti Nursyamsiah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
The Passivity of the operations function, when compared to the finance and marketing functions, has long been noted as one of the elements which can explain poor bussiness performance. The subordinate strate¬gic role often assigned to operations leads to a reactive posture. The proactive stance for manufacturing is likely to enhance overall business performance. The riset examined empirically the relationships between manufactur¬ing proactiveness and businees performance based on data collected from a sample of firms in the manufacturing industry. Based on the manufacturing strategy literature, we identify two mayor dimensions of manufacturing proactiveness:(1) the degree of manufacturing`s involvement in the strategic processes of the business unit, and (2) the degree of commitment to long-term program of investments in manufacturing structure and infrastructure aimed at building capabilities in anticipation of their need. The results of the study suggest that dimensions of manu¬facturing proactiveness are show distinguish between high and low performance firms. The firms that score highly on long-term investmens in structural programs coupled high levels of manufacturing invol¬vement in strategic processes and planned investments in infrastructural programs correlate with higher than average performance.Keywords: Manufacturing Involvement, Infrastructural Programs, structural Programs, Business Performance